2015
DOI: 10.1155/2015/310350
|View full text |Cite
|
Sign up to set email alerts
|

Early Cardiac Tamponade in a Patient with Postsurgical Hypothyroidism

Abstract: Pericardial effusion is a common cardiac manifestation of hypothyroidism, but effusion resulting in cardiac tamponade is extremely rare. We present a case of a 56-year-old African American woman with slurred speech and altered mental status that was initially suspected to have stroke. Her chest X-ray revealed cardiomegaly and subsequent echocardiogram showed a large pericardial effusion with echocardiographic evidence of cardiac tamponade. Clinically, patient did not have pulsus paradoxus or hypotension. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Reversible echocardiographic abnormalities are usually documented in a hypothyroid heart. Heart dilatation, reduced myocardial contractility, enlarged thickness of the interventricular septum and increase in the left ventricular volume had been described in the earlier studies [10] and in our study also the patients echocardiography picture had shown left ventricular hypertrophy and the dilatation of heart. This state usually mimics hypertrophic and dilated cardiomyopathies, but these abnormalities can be reversed by bringing the hypothyroid state to normal [11].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reversible echocardiographic abnormalities are usually documented in a hypothyroid heart. Heart dilatation, reduced myocardial contractility, enlarged thickness of the interventricular septum and increase in the left ventricular volume had been described in the earlier studies [10] and in our study also the patients echocardiography picture had shown left ventricular hypertrophy and the dilatation of heart. This state usually mimics hypertrophic and dilated cardiomyopathies, but these abnormalities can be reversed by bringing the hypothyroid state to normal [11].…”
Section: Discussionsupporting
confidence: 88%
“…Histopathological examination of the myocardium shows interstitial edema and swelling of the muscle fibers with loss of striations, which is a hallmark of myocardial muscle. The pericardial sac usually contains fluid rich in protein and mucopolysaccharides [10]. In our study, patient also we had the pericardial fluid analysis showing rich in proteins.…”
Section: Discussionsupporting
confidence: 48%
“…Common electrocardiographic findings of tamponade include decreased voltage with electrical alternans. Sinus bradycardia, T wave flattening has been known to be associated with hypothyroidism along with QT prolongation [2,5]. In our case the patient had a heart rate that varied between 50-70 bpm with a prolonged corrected QT interval of 495 ms in keeping with previously reported changes.…”
Section: Discussionsupporting
confidence: 87%
“…Pericardial effusion is characteristically transudative unless there is concomitant disease [2]. Echocardiographic changes of hypothyroidism include LV diastolic dysfunction with thick septa with separate E and A or inverted E/A on Doppler [2,5]. Longstanding untreated hypothyroidism can result in increased arterial stiffness leading to concentric hypertrophy as seen with our patient [6].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation